Mechanisms of the response of apple fruit to postharvest compression damage analyzed by integrated transcriptome and metabolome - Zhichao Yang; Menghua Lin; Xiangzheng Yang; Changqing Zhu; Di Wu; Kunsong Chen (Food Chemistry: X, 2023)
Apple fruit is susceptible to compression damage within the postharvest supply chain given its thin peels and brittle texture, which can result in decay and deterioration and have a substantial impact on its marketability and competitiveness. Thorough bioinformatics investigations are lacking on postharvest compression damage stress-induced alterations in genes and metabolic regulatory networks in fruits. In the present study, a comprehensive analysis of both the transcriptome and metabolome was conducted on 'Red Fuji' apples experiencing compression-induced damage. During the storage after damage has occurred, the gene expression of MdOFUT19, MdWRKY48, MdCBP60E, MdCYP450 and MdSM-like of the damaged apples was consistently higher than that of the control group. The damaged apples also had higher contents of some metabolites such as procyanidin A1, Dl-2-Aminooctanoic acid, 5-O-p-Coumaroyl shikimic acid and 5,7-Dihydroxy-3′,4′,5′-trimethoxyflavone. Analysis of genes and metabolites with distinct expressions on the common annotation pathway suggested that the fruit may respond to compression stress by promoting volatile ester and lignin synthesis. The above results can deepen the comprehension of the response mechanisms in apple fruits undergoing compression-induced damage.